Konstruksi Brand Identity Produk Lokal: Studi Strategi Komunikasi Pemasaran Pemerintah Negeri Morella - Vransisca Kissya; Alfonsa Renmaur (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Marketing communication strategy is an important element in business development, particularly in addressing the challenges of marketing local products. This study aims to examine the marketing communication strategies implemented by the Morella Village Government and Village-Owned Enterprises (BUMDES) in improving the marketing of Morella nutmeg juice products produced by local SMEs. The strategy was implemented through promotional mix activities to attract consumers both in Maluku and outside the region. This study employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Data were analyzed using the interactive analysis model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results showed that the Morella Village Government and BUMDES implemented marketing communication strategies through collaboration with government agencies and regional organizations, as well as information technology-based marketing approaches. The marketing strategies covered product, price, place, and promotion aspects, including advertising, sales promotion, personal selling, direct marketing, and public relations. The implemented marketing communication strategies were considered effective in improving the marketing performance of Morella nutmeg juice products and were consistent with the concept of integrated marketing communication.